(untitled) (Research, Society and Development, 2022)
Intraocular lymphoma is a malignant neoplasm, which commonly affects the uveal tract of dogs, most of the time, a consequence of the multicentric by the hematogenous spread of neoplastic lymphocytes. The symptoms are varied and the chronicity can cause serious eye problems such as glaucoma and loss of visual acuity. In view of the unusual occurrence of primary ocular lymphoma in dogs, the objective was to discuss the case of a dog with uveal involvement, presenting conjunctival congestion, increased episcleral vessels, hypopyon, hyphema and increased intraocular pressure. After seven days of conservative treatment, symptoms worsened, especially the intraocular pressure. The tutor returned only two months after the consultation with the sonographic report of neoplasia in the uvea. There was an increase in the ocular bulb, vascularization and corneal edema, posterior synechia, discomfort, loss of visual acuity and neoformation in the iris. Was opted for enucleation and the histopathology suggested large cell lymphoma in the uveal tract. Two years after surgery, no metastases were observed. It is concluded that lymphoma can affect the uveal tract primarily in dogs, demonstrating different clinical signs and, in addition, early diagnosis and correctly instituted treatment favor quality of life and survival of the affected.